2011
DOI: 10.1124/dmd.110.036129
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Overall Renal Tubular Secretion and Hepatic Clearance of Anionic Drugs and a Renal Drug-Drug Interaction Involving Organic Anion Transporter 3 in Humans by In Vitro Uptake Experiments

Abstract: ABSTRACT:The present study investigated prediction of the overall renal tubular secretion and hepatic clearances of anionic drugs based on in vitro transport studies. The saturable uptake of eight drugs, most of which were OAT3 substrates (rosuvastatin, pravastatin, pitavastatin, valsartan, olmesartan, trichlormethiazide, p-aminohippurate, and benzylpenicillin) by freshly prepared human kidney slices underestimated the overall intrinsic clearance of the tubular secretion; therefore, a scaling factor of 10 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 35 publications
1
70
0
Order By: Relevance
“…A good correlation between the predicted hepatic clearances of OATP substrates, estimated using an in vitro uptake assay with hepatocytes, and observed hepatic clearances has been well characterized Watanabe et al, 2009Watanabe et al, , 2010Watanabe et al, , 2011. Thus, OATP transporters are thought to play crucial roles as determinants of hepatic clearance of transporter substrates.…”
Section: Introductionmentioning
confidence: 95%
“…A good correlation between the predicted hepatic clearances of OATP substrates, estimated using an in vitro uptake assay with hepatocytes, and observed hepatic clearances has been well characterized Watanabe et al, 2009Watanabe et al, , 2010Watanabe et al, , 2011. Thus, OATP transporters are thought to play crucial roles as determinants of hepatic clearance of transporter substrates.…”
Section: Introductionmentioning
confidence: 95%
“…This is also implied in humans by a one-to-one correlation between in vivo non-renal clearances of 9 OATP substrates in humans and the predicted clearances from in vitro uptake assay with human cryopreserved hepatocytes. 19) Regarding statins, Watanabe et al have demonstrated that the overall hepatic clearance of 4 statins, pitavastatin, rosuvastatin, atorvastatin and fluvastatin is mainly dominated by the hepatic uptake process. 20) Pitavastatin and rosuvastatin are not metabolized in rats and mainly excreted into bile in an unchanged form, whereas atorvastatin and fluvastatin, which are both reported to be OATP substrates, are extensively metabolized by CYP3A4 and CYP2C9, respectively.…”
Section: Ps CL β Ps Ps Clmentioning
confidence: 99%
“…Kidney slices can be used to investigate drug uptake at the basolateral membrane but not tubular reabsorption (37,38). An advantage of kidney slices is that the interactions of multiple substrates, inhibitors and endogenous transporters can be investigated in this complex system (38).…”
Section: Kidney Slicesmentioning
confidence: 99%
“…An advantage of kidney slices is that the interactions of multiple substrates, inhibitors and endogenous transporters can be investigated in this complex system (38). Imaging technology (e.g.…”
Section: Kidney Slicesmentioning
confidence: 99%
See 1 more Smart Citation